1985
DOI: 10.2172/6194571
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mercury, arsenic, and selenium in the product streams of the Pacific Northwest Laboratory 6-kg retort

Abstract: The objective of this program is to determine how retorting process parameters affect the partitioning of Hg, As, Se, and Cd from raw o11 shale to spent shale, shale oil, retort water, and offgas. For each of the elements, the objective of this study is to 1) determine the distribution coefficients for each product stream; 2) identify the chemical forms in water, gas, and oil streams, with particular emphasis on inorganic or organometallic species known to be or suspected of being carcinogenic, toxic, or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1989
1989
1993
1993

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…Comparing these results to those observed during the retorting of the three aforementioned Australian shales revealed some differences and some similarities. The selenium in Julia Creek (10) (19) had a tendency to distribute almost equally into the shale oil and the retort water in a manner similar to the behavior in this study's eastern shale; however, contrary to the Australian study findings (10,19) that selenium was progressively mobile as temperatures increased in the Julia Creek, Condor, and Rundle oil shales, this study found little dependency on heating rates or maximum temperatures.…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…Comparing these results to those observed during the retorting of the three aforementioned Australian shales revealed some differences and some similarities. The selenium in Julia Creek (10) (19) had a tendency to distribute almost equally into the shale oil and the retort water in a manner similar to the behavior in this study's eastern shale; however, contrary to the Australian study findings (10,19) that selenium was progressively mobile as temperatures increased in the Julia Creek, Condor, and Rundle oil shales, this study found little dependency on heating rates or maximum temperatures.…”
Section: Resultscontrasting
confidence: 52%
“…Selected samples of raw shale, spent shale, shale oil, and retort water were analyzed for total arsenic and selenium (19); the shale oil and retort water samples were also analyzed for mercury by INAA. In addition, a neutron multiplier system was used on selected shale oil samples specifically for selenium analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation